Paediatric motor phenotypes in early‐onset ataxia, developmental coordination disorder, and central hypotonia. (17th September 2019) - Lawerman, Tjitske F; Brandsma, Rick; Maurits, Natalia M; Martinez‐Manzanera, Octavio; Verschuuren‐Bemelmans, Corien C; Lunsing, Roelineke J; Brouwer, Oebo F; Kremer, Hubertus PH; Sival, Deborah A
Abstract : Aims: To investigate the accuracy of phenotypic early‐onset ataxia (EOA) recognition among developmental conditions, including developmental coordination disorder (DCD) and hypotonia of central nervous system origin, and the effect of scientifically validated EOA features on changing phenotypic consensus. Method: We included 32 children (4–17y) diagnosed with EOA ( n =11), DCD ( n =10), and central hypotonia ( n =11). Three paediatric neurologists independently assessed videotaped motor behaviour phenotypically and quantitatively (using the Scale for Assessment and Rating of Ataxia [SARA]). We determined: (1) phenotypic interobserver agreement and phenotypic homogeneity (percentage of phenotypes with full consensus by all three observers according to the underlying diagnosis); (2) SARA (sub)score profiles; and (3) the effect of three scientifically validated EOA features on phenotypic consensus. Results: Phenotypic homogeneity occurred in 8 out of 11, 2 out of 10, and 1 out of 11 patients with EOA, DCD, and central hypotonia respectively. Homogeneous phenotypic discrimination of EOA from DCD and central hypotonia occurred in 16 out of 21 and 22 out of 22 patients respectively. Inhomogeneously discriminated EOA and DCD phenotypes (5 out of 21) revealed overlapping SARA scores with different SARA subscore profiles. After phenotypic reassessment with scientifically validated EOA features, phenotypic homogeneity changed from 16 to 18 patients. Interpretation: In contrast to complete distinction between EOA and central hypotonia, the paediatric motor phenotype did not reliably distinguish between EOA and DCD. Reassessment with scientifically validated EOA features could contribute to a higher phenotypic consensus. Early‐onset ataxia (EOA) and central hypotonia motor phenotypes were reliably distinguished. EOA and developmental coordination disorder (DCD) motor phenotypes were not reliably distinguished. The EOA and DCD phenotypes have different profiles of the Scale for Assessment and Rating of Ataxia. Abstract : Early‐onset ataxia (EOA) and central hypotonia motor phenotypes were reliably distinguished. EOA and developmental coordination disorder (DCD) motor phenotypes were not reliably distinguished. The EOA and DCD phenotypes have different profiles of the Scale for Assessment and Rating of Ataxia. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Baxter on page 11 of this issue. Video Podcast: https://www.youtube.com/watch?v=SfBS16PxEao Resumen: Fenotipos pediátricos motores en ataxia de inicio temprano, trastorno del desarrollo de la coordinación e hipotonía de origen central: Objetivos: Investigar la precisión del reconocimiento fenotípico de ataxia de inicio temprano (EOA) con respecto a trastornos del desarrollo, incluido el trastorno del desarrollo de la coordinación (TDC) y la hipotonía de origen central. Investigar el efecto de las características científicamente validadas de EOA sobre el consenso fenotípico entre los evaluadores. Método: Se incluyeron 32 niños (4‐17 años) diagnosticados con EOA (n = 11), TDC (n = 10) e hipotonía central (n = 11). Tres neurólogos pediátricos evaluaron de forma independiente el comportamiento motor grabado en video en cuanto a las características fenotípica y cuantitativa (utilizando la Escala de evaluación y calificación de la ataxia [SARA]). Determinamos: (1) coincidencia fenotípica entre los observadores y homogeneidad fenotípica (porcentaje de fenotipos con consenso total de los tres observadores según el diagnóstico subyacente), (2) perfiles de (sub)puntajes en el SARA y (3) el efecto sobre el consenso fenotípico de tres características de EOA validadas científicamente. Resultados: La homogeneidad fenotípica ocurrió en 8 de 11, 2 de 10 y 1 de 11 pacientes con EOA, DCD e hipotonía central, respectivamente. La discriminación fenotípica homogénea de EOA con respecto a TDC e hipotonía central se produjo en 16 de 21 y 22 de 22 pacientes, respectivamente. Los fenotipos EOA y TDC que no fueron discriminados de manera homogénea por los observadores (5 de 21) revelaron superposición en los puntajes del SARA con diferentes perfiles en los subpuntajes del SARA. Después de una reevaluación fenotípica con características EOA científicamente validadas, la homogeneidad fenotípica cambió de 16 a 18 pacientes. Interpretación: En contraste con la distinción completa entre EOA e hipotonía central, el fenotipo motor pediátrico no distinguió confiablemente entre EOA y TDC. La evaluación en base a características EOA científicamente validadas podría contribuir a un mayor consenso fenotípico. Resumo: Fenótipos motores pediátricos na ataxia de início precoce, transtorno do desenvolvimento da coordenacão, e hipotonia central: Objetivos: Investigar a acurácia do reconhecimento fenotípico da ataxia de início precoce (AIP) entre condições desenvolvimentais, incluindo o transtorno do desenvolvimento da coordenação (TDC) e a hipotonia de origem no sistema nervoso central, e o efeito de aspectos cientificamente validados da AIP na modificação do consenso fenotípico. Método: Incluímos 32 crianças (4–17a) diagnosticadas com AIP ( n =11), TDC ( n =10), e hipotonia central ( n =11). Três neurologistas pediátricos avaliaram de maneira independente por meio de vídeo o comportamento motor tanto por meio do fenótiopo quanto quantitativamente (usando a Escala para Avaliação e Pontuação da Ataxia) [EAPA]). Determinamos: (1) a concordânica fenotípica inter‐observadores e a homogeneidade fenotípica (porcentagem de fenótipos com consenso completo pelos três observadores de acordo com o diagnóstico de base, (2) perfis segundo os (sub)escores da EAPA, e (3) o efeito de três aspectos cientificamente validados da AIP sobre o consenso fenotípico. Resultados: A homogeneidade fenotípica ocorreu em 8 entre 12, 2 entre 10, e 1 entre 11 pacientes com AIP, TDC, e hipotonia central, respectivamente. A discriminação fenotípica homogênea da AIP com relação ao TDC e hipotonia central ocorreu em 16 entre 21 e 21 entre 22 pacientes, respectivamente. A discriminação não homogêna dos fenótipos AIP e TDC (5 em 21) revelou escores da EAPA que sobrepõem com diferentes perfis de subescores da EAPA. Após reavaliação fenotípica com aspectos cientificamente validados da AIP, a homogeneidade fenotípica mudou de 16 para 18 pacientes. Interpretação: Em contraste com a completa distinção entre AIP e hipotonia central, o fenótipo motor pediátrico não distinguiu confiavelmente entre AIP e TDC. A reavaliação com aspectos cientificamente valiaddos da AIP pode contribuir para um maior consenso fenotípica. contrast to complete distinction between EOA and central hypotonia, the paediatric motor phenotype did not reliably distinguish between EOA and DCD. eassessment with scientifically validated EOA features could contribute to a higher phenotypic consensus.